Robot-assisted inguinal sentinel lymph node biopsy in primary yolk sac tumor of the vulva. (September 2018) - Kim, Se Ik; Kim, Ranah; Seong, Jisu; Kim, Hee Seung
Abstract: Background: Primary yolk sac tumor (YST) of the vulva is extremely rare and only introduced in case reports [1 ]. For those, routine inguinal lymph node dissection (LND) in absence of palpable inguinal lymph node is questionable. To avoid complications of inguinal LND, such as lymphedema, inguinal sentinel lymph node biopsy (SLNB) can be considered [2, 3 ]. Since recent studies reported feasibility of robot-assisted inguinal lymphadenectomy [4 ], we showed the surgical procedures of robot-assisted inguinal SLNB. Video: A 33-year-old woman with vulvar YST was referred. Two 2 cm sized masses were founded in right vulvar area, and lymph node enlargement was detected in only right external iliac area on imaging studies. Thus, we planned robot-assisted surgical treatment including inguinal SLNB using the fluorescent dye indocyanine green (ICG) during surgery for the vulvar YST. First, we performed intradermal and peri-tumoral injection of 1 ml solution including 1.25 mg of ICG at each 2, 5, 7, and 10 o'clock position for the two tumors. Fifteen minutes later, three-arm robotic surgical system was installed on right thigh. Dissecting the subcutaneous space under the Scarpa's fascia towards the inguinal ligament, one fluorescent inguinal sentinel lymph node was identified and excised, which showed no tumor on pathologic examination (Fig. 1 ). Results: The procedure time was 70 minutes, and she underwent subsequent robot-assisted pelvic and para-aortic lymphadenectomy and wide local excision of the vulva. Conclusion: Robot-assisted inguinal SLNB is feasible. It may be an alternative to inguinal LND for avoiding relevant complications in patients with vulvar malignancy. Highlights: Primary yolk sac tumor of the vulva is extremely rare. Inguinal lymphadenectomy is related with the high level of complications. Routine inguinal lymphadenectomy in absence of palpable lymph node is questionable. Robot-assisted inguinal sentinel lymph node biopsy is feasible as an alternative.